bones & flesh - Hammerton, Kerry (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My collection encompasses personal relationships, intimacy, and the erotic, as well as more narrative poems grounded in landscapes, including urban and internal landscapes. Some were written in conversation with other poems or pieces of prose such as the stories of Noy Holland. I use free verse forms influenced by various prose poems as well as by the musical/tonal forms of poets such as Lorca. Other styles and influences include the darkness and directness of Spanish poetry particularly Rafael Alberti (esp. his book Concerning the Angels); and the confident and reflective style of Romanian poet Nina Cassian.
Keywords: Uncatalogued